ENHANCING PARTICIPATION IN INDONESIA'S ISLAMIC CAPITAL MARKET: EXPLORING TECHNOLOGY ACCEPTANCE, SOCIO-PSYCHOLOGICAL FACTORS, AND ISLAMIC FINANCIAL LITERACY - Ibrahim, Muhammad Hanif; Agung Putri, Akmalia Lutfiaturrosyida; Hasanah, Imas; Agustin, Apia Dewi; Rosyida, Afnani (Jurnal Akuntansi dan Keuangan Indonesia, 2025)
Background: This research aims to examine the factors influencing Indonesian Muslims' intention to invest in the Islamic capital market by synthesizing three theoretical frameworks: the Technology Acceptance Model (TAM), the Theory of Planned Behavior (TPB), and Islamic Financial Literacy (IFL). Methods: The study utilizes a sample of 250 participants with previous experience in Islamic investment, employing Partial Least Squares Structural Equation Modeling (PLS-SEM) for hypothesis testing and model evaluation. Findings: The findings indicate that perceived convenience substantially influenced perceived usefulness and ease of use. Moreover, perceived usefulness, Islamic financial literacy, and past behavior significantly and positively affect investment attitudes, which subsequently influences the intention to employ Islamic capital market instruments. Notably, subjective norms, perceived ease of use, and perceived behavioral control do not significantly influence attitudes, indicating that individual experiences and perceived value is more crucial than social and control-related factors in determining investment decisions. Conclusion: This study emphasizes the necessity for stakeholder initiatives, especially in financial education and digital service optimization, to improve Muslim investor engagement, and highlights the importance of user experience and perceived value. Novelty/Originality of this article: This research enhances the literature by presenting a comprehensive and integrated model encompassing cognitive, affective, and behavioral components, while also introducing a higher-order construct approach for measuring Islamic financial literacy. It offers strategic insights for creating inclusive and effective Sharia-compliant investment ecosystems in Indonesia